Boenninghausen's Therapeutic Pocket Book and Musculoskeletal Pain - Katarmal, Daisy (Homœopathic Links, 2019)
This paper intends to throw light on Boenninghausen's method and his less often used repertory: Boenninghausen's Therapeutic Pocket Book. This is one of the first repertories and is considered an authentic work of Boenninghausen. However, Therapeutic Pocket Book is less used in practice because of certain points of criticisms; an attempt has been made to give a rationale for these points. Another point of controversy is discussed that may be frequently encountered in practice: whether to consider the disease pathology or solely depends on the totality of symptoms to work out a case homeopathically. The practical use of Therapeutic Pocket Book has been illustrated with a study in which it is observed that the homoeopathic treatment done using Boenninghausen's method is able to reduce the intensity of pain in patients with musculoskeletal pain.
Keywords: Boenninghausen's Therapeutic Pocket Book; pain; totality